Understanding veteran barriers to specialty outpatient PTSD clinical care. (April 2023) - Rozek, David C.; Steigerwald, Victoria L.; Baker, Shelby N.; Gross, Georgina; Maieritsch, Kelly P.; Hoff, Rani; Harpaz-Rotem, Ilan; Smith, Noelle B.
Abstract: Objective: Veterans seeking treatment for posttraumatic stress disorder (PTSD) commonly report general and veteran-specific barriers to treatment such as stigma and challenges with navigating the Veterans Health Affairs (VHA) system. This study aimed to characterize barriers endorsed by a national sample of veterans seeking care in VHA PTSD specialty outpatient clinics, as well as to examine the impact of demographics on endorsed barriers. Methods: This study included 17, 069 veterans referred to PTSD specialty outpatient clinics in the VHA during Fiscal Year 2019. Barriers to care, demographics, clinical concerns, and PTSD symptom severity (PCL-5) were assessed at intake. Results: Veterans (mean age=47.6 years, 83.3% male) endorsed an average of 2.39 barriers. The most commonly endorsed barriers included difficulty interacting with others (37.9%), difficulty being in public (33.8%), work (30.3%), concern for finances (20%), and difficulty getting out of bed (19.5%). A significant minority of veterans (22%) endorsed no barriers. Male sex (23.1%) and White race (23.6%) were associated with a greater likelihood of reporting no barriers. Conclusions: These findings indicate the need for a comprehensive approach to addressing multi-faceted barriers for veterans seeking treatment in PTSD specialty clinics. Findings also highlight the potential importance of tailoring strategies to reduce barriers based on demographic and clinical characteristics such as race, sex, and degree of avoidance. Future research should seek to longitudinally examine the impact of barriers on treatment engagement. Highlights: Barriers to care was examined for 17, 000 + military veterans. Barriers were identified for specialty PTSD treatment. Just over 20% of veterans endorsed no barriers to care.